الإبداع في قطاع المكتبات - شعبان, جمال (جامعة الوادي - University of Eloued, 2022)
الهدف: إبراز أهمية ودور ومهام ومجالات الإبداع في قطاع المكتبات. فالمكتبات في حاجة ماسة إلى الإبداع في خدماتها من أجل مواكبة العصر. وقد بات الإبداع مقومًا أساسيًا للمكتبات الحديثة حتى تضطلع بأدوارها وتقوم بمهام جديدة، إجبارًا وليس خيارًا. وهذا، لن يكون ألا بمورد بشري مبدع، يملك الأفكار والمهارات تسمح له بحل مشكلاتها ورفع تحدياتها. وتطوير خدمات جديدة، تضمن استمرار المكتبات وجودة أدائها والمحافظة على مستعمليها. المنهجية: استخدمنا المنهج الوصفي المعتمد على البحث الوثائقي، سعيًا إلى توطين الابداع في قطاع المكتبات. النتائج: محاولة تغيير الصورة النمطية الساكنة السائدة في مكتباتنا بصورة حيوية فاعلة وتحديد مستلزمات ممارسة الإبداع، كأداة وآلية حديثة تساعد المكتبات على تخطي صعوباتها وتطوير خدماتها تكيفًا مع عصرها. Objective: To highlight the importance, role, tasks and areas of creativity in the library sector. Libraries are in dire need of creativity in their services in order to keep pace with the times. Creativity has become an essential ingredient for modern libraries to undertake new roles and tasks, it’s forcing not an option. This will only be with a creative human resource, who has ideas and skills that allow him to solve problems, raise challenges, and develop new services that ensure the continuity of libraries, the quality of their performance, and the preservation of their users. Method: We used the descriptive approach based on documentary research, seeking to localize creativity in the library sector. Results: an attempt to change the static stereotype in our libraries in that vital and effective way, and determining the requirements for practicing creativity.
المقاربة وتطوير الخدمات والنشاطات
مقال
Keywords: مكتبة، خدمة مكتبية، نشاط مكتبي، إبداع، إبداع مكتبي; library, library service, library activity, creativity, Librarian creativity